2019
DOI: 10.1080/15384047.2018.1564558
|View full text |Cite
|
Sign up to set email alerts
|

Lamc1 promotes the Warburg effect in hepatocellular carcinoma cells by regulating PKM2 expression through AKT pathway

Abstract: Hepatocellular carcinoma (HCC), the most common aggressive malignancy of liver, is the third leading cause of cancer death across the world. Laminin gamma 1 (Lamc1), encodes laminin-γ1, an extracellular matrix protein involved in various progresses such as tumor cell proliferation and metabolism. In the present study, high expression of Lamc1 and PKM2 was observed in tumor tissues of HCC patients. In vitro, down-regulation of Lamc1 inhibited proliferation of HCC cells by promoting cell death, reduced glucose c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 40 publications
(38 reference statements)
1
42
0
Order By: Relevance
“…Increased glycolysis, which is also called the “Warburg effect” [29, 30], has been found in several types of cancer and facilitates metastatic dissemination [31]. MiRNAs play an important role in the process of regulating glycolysis in cancer cells; for example, miR-143 can increase glucose metabolism and promote cell proliferation by targeting HK II directly in lung tumors [32].…”
Section: Discussionmentioning
confidence: 99%
“…Increased glycolysis, which is also called the “Warburg effect” [29, 30], has been found in several types of cancer and facilitates metastatic dissemination [31]. MiRNAs play an important role in the process of regulating glycolysis in cancer cells; for example, miR-143 can increase glucose metabolism and promote cell proliferation by targeting HK II directly in lung tumors [32].…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence has suggested that increased glycolysis is a hallmark of cancer cells [ 6 ]. Even under normal oxygen concentrations, the rate at which cancer cells metabolize glucose through glycolysis increases compared to normal cells [ 7 , 8 ]. This metabolic change increases glucose uptake and lactate production, thereby affecting cell growth, proliferation, angiogenesis, and invasion [ 5 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The protein (ITGA3) contains both up-and down-regulated glycosylation sites ( Figure 1D). LAMC1 was reported to be involved in cell proliferation, angiogenesis, growth, migration and invasion 11,12 . Remarkably, majority of the 9 aberrant glycoproteins in the key interaction module were enriched in ECM-receptor interaction pathways ( Figure 1D Coronavirus GX_P2V-induced alteration in protein glycosylation are prevalent in infected cells N-linked glycosylation was involved in multiple biological processes, such as receptor interactions, immune responses, protein secretion and transport, cell adhesion, signal transduction, etc.…”
Section: Resultsmentioning
confidence: 99%